Population dynamics and production of small, marine copepods in highly seasonal Arctic and sub-Arctic environments - Barth-Jensen, Coralie (UiT The Arctic University of Norway, 2023)
Small copepods (≤ 2 mm) are highly abundant mesozooplankton in Arctic and sub-Arctic marine ecosystems. However, small copepods are generally underestimated in zooplankton studies because of the use of large-meshed nets (≥ 180-µm mesh size) and are relatively poorly studied compared to large copepods. This thesis investigates the egg hatching rates, population dynamics and production rates of three abundant small copepod species in high-latitude ecosystems: Oithona similis , Microsetella norvegica , and Microcalanus pusillus . The egg hatching rates were investigated at between 1.3°C and 13.2°C by incubating ovigerous females. Field work was conducted in three sub-Arctic fjords and around Svalbard to obtain the biomass, age structure, and production of the populations sampled with a 64-µm mesh net. The egg hatching rates had various species-specific temperature response, which suggested different thermal plasticity among the three similar-sized species. The population dynamics of the three studied species also showed different patterns. M. norvegica has a time-limited reproduction resulting in a short but intense reproductive season and overwintering as adults. In contrast, O. similis and M. pusillus have continuous reproduction, where winter is used as recruitment period for a second generation. The most important findings of this thesis is the high biomass and production revealed by the quantitative sampling of small copepods. The biomass and production of small copepods could be equal to or even higher than that of large copepods, regardless of the season but with large spatial and interannual variations. In Balsfjord, the total production of the three small copepods could equal 0.3 to 27% of the primary production, meaning that small copepods have a significant role in the food web and carbon cycling of high-latitude ecosystems.